A experimental characterization of seismic plus thermal energy retrofitting techniques for masonry infill walls - Furtado, André (2023)
The renovation and refurbishment of existing envelopes of existing RC buildings are usually performed, focusing only on improving their structural or thermal energy characteristics. However, international concern about the sustainability and resilience of existing building structures demands the rethinking of retrofitting techniques that tackle both aspects simultaneously, making the envelopes more energy efficient and seismic safer. Based on this motivation, a testing campaign was carried out to validate the efficiency of novel seismic plus energy retrofitting techniques. Five full-scale specimens were built, three of them with seismic plus energy retrofitting and two of them with solutions developed to improve each case. The five specimens were subjected to pure OOP quasi-static loadings until reached the collapse or partial collapse. The results of the retrofitted walls were compared with a reference specimen (i.e. non-retrofitted) to assess the efficiency of each solution. From the results, it was observed that the novel combined retrofitting can improve the thermal transmittance of the wall by around 70%, and the strength and deformation capacity by up to 125% and 340%, respectively.